Investigating clinicians' determinants of antimicrobial prescribing behaviour using the Theoretical Domains Framework. (April 2022) - Talkhan, H.; Stewart, D.; McIntosh, T.; Ziglam, H.; Abdulrouf, P.V.; Al-Hail, M.; Diab, M.; Cunningham, S.
Summary: Aim: To identify and quantify potential determinants of antimicrobial prescribing behaviour, using the Theoretical Domains Framework (TDF). Methods: A cross-sectional survey involving doctors (∼4000) and pharmacists (∼400) working within Hamad Medical Corporation (HMC), Qatar. An online questionnaire, developed with reference to the TDF, included: personal and practice demographics, and Likert statements on potential determinants of antimicrobial prescribing practice. Analysis included principal component analysis (PCA), descriptive and inferential statistics. Results: In total, 535 responses were received, 339 (63.4%) from doctors. Respondents were predominantly male, 346 (64.7%). Just over half ( N = 285, 53.3%) had ≤5 years' experience. PCA showed a three-component (C) solution: 'Guidelines compliance' (C1), 'Influences on practice' (C2) and 'Self-efficacy' (C3). The scales derived for each component had high internal consistency (Cronbach's alphas >0.7), indicating statistical appropriateness for developing scales. Respondents generally scored highly for 'Guidelines compliance' and 'Self-efficacy'. The lowest levels of positive scores were in relation to the items within the 'Influences on practice' component, with particular focus on TDF domains, environmental context and resources, and social influences. Inferential analysis comparing component scores across demographic characteristics showed that doctors, the more qualified and those with greater experience, were more likely to be positive in responses. Conclusions: This study has identified that environmental context and resources, and social influences, with an emphasis on pharmacists and early career clinicians, may be useful targets for behaviour change interventions to improve clinicians' antimicrobial prescribing, thereby reducing antimicrobial resistance rates. Such interventions should focus on appropriate linked behaviour-change techniques.